A Cross-Sectional Study on Smartphone Use among Children during COVID-19 Lockdown in Tamilnadu, India - Gopi Rajendhiran; Mrs. Bijulalkshmi P; Dr. Vikhram Ramasubramanian; Dr. Mathumathi S; Mr. Kannan (Analitika: Jurnal Magister Psikologi UMA, 2023)
Smartphones have made internet available at our fingertips. More children around the world are born mobile ready especially kids born after 2015 (Gen Alpha). The COVID induced lockdown had robbed children of other means of entertainment and combined with the easy access to smartphones due to the online classes, the overuse of smartphones is a concept of great concern to parents. An online survey was conducted in India among parents about the usage of smartphone in their children and the parents also filled out a self-constructed questionnaire to find the levels of smartphone addiction in their children. 1330 people participated in the study and their responses were used to analyze the various factors contributing to smartphone overuse. The amount of time spent in smartphone has increased exponentially during COVID 19 induced lockdown, with 14.7% of children spending 5 - 6 hours per day and a small percentage of children (3.3%) spending more than 9 hours per day. Children who owned a smartphone and adolescent children have higher scores in the smartphone addiction scale.